2014
DOI: 10.1002/adma.201401573
|View full text |Cite
|
Sign up to set email alerts
|

A First Implementation of an Automated Reel‐to‐Reel Fluidic Self‐Assembly Machine

Abstract: A first automated reel‐to‐reel fluidic selfassembly process for macroelectronic applications is reported. This system enables high‐speed assembly of semiconductor dies (15 000 chips per hour using a 2.5 cm‐wide web) over large‐area substrates. The optimization of the system (>99% assembly yield) is based on identification, calculation, and optimization of the relevant forces. As an application, the production of a solid‐state lighting panel is discussed, involving a novel approach to apply a conductive layer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 36 publications
(52 reference statements)
0
58
1
Order By: Relevance
“…39 And even more resource efficient parallel and unsupervised assembly processes can be also potentially adopted for this. [26][27][28][29] Hence, the assembly process may be further streamlined substantially lowering the associated costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 And even more resource efficient parallel and unsupervised assembly processes can be also potentially adopted for this. [26][27][28][29] Hence, the assembly process may be further streamlined substantially lowering the associated costs.…”
Section: Discussionmentioning
confidence: 99%
“…So far such integration has been demonstrated only for micrometer-scale components, 12,[19][20][21][22][23][24][25] and it has been shown that heterogeneous integration can be done in a very efficient way by parallel and unsupervised self-assembly. [26][27][28][29] Micro-and nanoscale components are typically fabricated on rather thick (down to 25 lm, typically 200-300 lm thick) and large (down to 25 lm, typically 5-15 mm lateral dimensions) dies due to practical limitations regarding die a) Present address: International Iberian Nanotechnology Laboratory, Av.…”
Section: Introductionmentioning
confidence: 99%
“…A non-contact micro-assembly method provides an advantage at this point: self-assembly enables organizing components into patterns autonomously, without a direct mechanical contact [1]. Part presentation can be performed in a stochastic [2,3] or directed fashion [4][5][6] in self-assembly. In stochastic presentation approach, the parts are manipulated randomly by agitation or vibration.…”
Section: Introductionmentioning
confidence: 99%
“…13 The process is compatible with various types of chip attachment and assembly methods including solder bump based interconnects, flip-chip die attach, robotic pick-andplace, or engineered self-assembly using molten solder. 14,15 In the demonstrated case, we used a semi-automated pick-andplace process. The depicted demonstrator contains a total number of 5 analog MEMS microphones (3.76 Â 2.95 Â 1.2 mm, Knowles SPU0414HR5H-SB).…”
mentioning
confidence: 99%